2023
DOI: 10.1186/s42490-023-00067-5
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet image scattering based glaucoma detection

Abstract: Background The ever-growing need for cheap, simple, fast, and accurate healthcare solutions spurred a lot of research activities which are aimed at the reliable deployment of artificial intelligence in the medical fields. However, this has proved to be a daunting task especially when looking to make automated diagnoses using biomedical image data. Biomedical image data have complex patterns which human experts find very hard to comprehend. Against this backdrop, we applied a representation or f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“… State‐of‐the‐art performance: empirical studies have shown that wavelet scattering transform often outperforms traditional texture feature extraction methods, such as gray‐level co‐occurrence matrix and local binary patterns, in various pattern classification tasks. 57 , 58 , 59 …”
Section: Methodsmentioning
confidence: 99%
“… State‐of‐the‐art performance: empirical studies have shown that wavelet scattering transform often outperforms traditional texture feature extraction methods, such as gray‐level co‐occurrence matrix and local binary patterns, in various pattern classification tasks. 57 , 58 , 59 …”
Section: Methodsmentioning
confidence: 99%
“…Agboola et al proposed wavelet image scattering as a method to obtain low-variance representations within a specific class using 2D channel representations of retinal fundus images. The objective was to detect glaucoma and demonstrate the effectiveness of wavelet image scattering in generating strong and streamlined representations of retinal fundus image data [ 35 ]. Abdel-Hamid proposed an adapted VGG16 network with transfer learning to classify retinal images into good or bad quality categories [ 36 ].…”
Section: Related Workmentioning
confidence: 99%